Toxicity screening using Brine Shrimp Lethality Test (BST) of some benalu species traditionally utilized to treat tumour in Indonesia. - Mae Sri Hartati W Mae Sri Hartati W (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background : Traditionally some benalu species were used to treat tumour in Indonesia. Some research report indicated the present of anti tumour activity, although its toxicity study by BST was not performed yet. It is necessary to observe the toxic level of the benalu leaves and whether they are safe to be consumed. Objectives : To determine the toxic level of species of benalu leaves (Dendrophtoe pentandra L. Miq. (1), Macrosolen tetragonus (bL) Miq. (2 and 7), Helixanthera parasitica Lour. (3), Dendrophtoe falcate (Lf.) Ettings (4), Dendrophtoe constricta Dans. (5), Macrosolen cochinchinensis (Lour). Tiegh. (6))Methods : The leaves of benalu were separately extracted with chloroform, followed by methanol. The chloform and methanol extracts toxicity level were screened using Brine Shrimp Lethality Test (BST) at the dose of 1500, 1000 and 500 ug/mI. The level of the toxicity was determined by counting the death percentage of the Artemia saline larvae after 24 hours of adding the extract at the dose indicated. The extract was considered toxic when 100% A. saline larvae was killed at the dose < 1000 ug/ml, and the extract was mildl toxic when 100% death percentage was observed at the dose of 1500 ug/ml.Results : Practically all the chloroform extracts were non toxic since they were not able to kill 100% A. saline larvae at the dose of 1000 ug/mI. Although when the doses were raised to 1500 ug/mI, the 100% death percentage was still not obtained. Similarly, the methanol extracts were also non toxic at the dose of 1000 ug/ml. However, M. cochinchinensis (6) and M. tetragonus (7) were considered to be mild) toxic as their methanol extracts were able to kill 100% A. saline larvae when the dose was raised to 1500 ug/mI.Conclusion: The different test result (at 1500 ug/mI) shown by two methanol extracts of similar species M. tetragonus {2b (killed 52%) & 7b (100%)} should give an idea that the benalu are practically non toxic and save to be consumed for tumor treatment.Key words : toxicity screening, brine shrimp lethality test (bst) - benalu leaves - benalu hosts - anti tumor.